Consumer awareness and perceptions about e-waste management in semi-urban area of northern Tamil Nadu: A mixed-method approach - Boopathy Nisha; Shikha Shajil; Ruma Dutta; Timsi Jain (Wolters Kluwer Medknow Publications, 2022)
BACKGROUND: The increased use of electronic devices has caused a rise in the generation of e-waste, which is detrimental to the environment and human health. This study aimed to assess consumer awareness, perception, and disposal methods of e-waste management and its determinants in a semi-urban area of northern Tamil Nadu. MATERIALS AND METHODS: It was a mixed-method approach using a sequential explanatory technique with both quantitative and qualitative methods in adult e-consumers. Quantitative data were collected from 350 participants selected via simple random sampling using score-based semi-structured questionnaire. Qualitative data were obtained purposely from eight selected consumers such as recyclers, local leaders, and importers of electronics using key informant interviews. Sociodemographic details and disposal practices were summarized as frequencies and percentages. The independent t-test and linear regression analysis were used to obtain the determinants. Qualitative data were analyzed thematically. RESULTS: Of the 350 participants (208 males and 142 females), the majority (76%), had good knowledge of e-waste management. Consumers (70%) predominantly had a positive perception. Selling e-wastes to scrap dealers (35%) and disposing of household wastes (21%) were common disposal methods. Male gender, higher education (≥10th grade), and skilled and professional workers were significant determining factors of good knowledge and positive perception toward e-waste management. CONCLUSION: There is a need for those in authority to pay special attention to sensitizing the public to the disposal of e-waste practices, ill effects of e-wastes, segregation at collection sites, legislations and laws on e-waste to consumers, and the establishment of disposal sites.